Uso de revestimentos comestíveis ativos com nanofibras celulosídicas de casca de arroz na pós-colheita de frutas - Careli-Gondim, Ítalo (2017)
With the large accumulation of non-biodegradable packaging waste, along with the difficulty of recycling most of them, the stimulus to develop biodegradable packaging from renewable sources and contributes to the preservation of fruit quality. The present study aimed to produce and characterize edible films based on rice flour, pectin and sorbitol, applying the casting technique, and to evaluate the effect of the addition of rice husk celluloid nanofibers and potassium sorbate solution. The films were evaluated for mechanical properties, water vapor permeability, pH, opacity and water solubility, and characterized the best thermal properties, wettability and microstructural characteristics to be applied in fruits as an edible coating in order to increase the time Postharvest. Strawberry, guava and avocado were coated for 20 days, a post-harvest study was carried out with respect to the physiochemical and physiological quality of the respiratory rate, loss of mass, pH, soluble solids, titratable acidity, ascorbic acid content, Antioxidant activity, total phenolics, color, texture and pigments (chlorophyll and anthocyanins). The films with 5 g of rice flour, 5 g of pectin, 25 mL of sorbitol solution, 3 mL of rice husk cellulosic nanofibres and 2 mL of potassium sorbate solution show good processability, allowing the production of edible coating, With mechanical properties, water vapor barrier and opacity that may contribute to prolong post-harvest time of fruits. It is possible to double the shelf life of strawberries by applying the edible coating. The coating contributed to delay the ripening of the avocados, reducing the respiratory rate, the loss of mass, helping to maintain the firmness of the fruits and delaying the ripening of the fruits for 12 days with the application of the coating. The edible coating contributed to retarding the metabolism of the coated guava by doubling the ripening start time along the refrigerated storage.